Identification of Secondary Metabolites of Garlic Peels Extract (Allium sativum) - Mercyska Suryandari Mercyska; Galuh Gondo Kusumo; Ade Ferdinan (Jurnal Komunitas Farmasi Nasional, 2022)
The use of garlic often only makes use of the root part, while the garlic skin is often thrown away without optimal utilization and ends up as waste. Garlic skin has the potential to be developed as a treatment, one of which is for cholesterol because it contains phytochemical compounds. Previous studies have shown that using different solvents during the extraction process will produce different secondary metabolites. So the purpose of this study was to find out the secondary metabolites of garlic skin extract (Allium sativum L.) qualitatively when extracted using 5 different solvents. In this research, the method used was phytochemical screening on garlic skin extract (Allium sativun L.). n-Hexane, Ethyl Acetate, Acetone, 96% Ethanol, and Chloroform using remaceration extraction method separately. The results showed that the yield value was 0.90%; 1.34%; 1.00%; 3.90%; 1.20%. The results showed that the n-Hexane extract of garlic (Allium sativum L.) peels contained steroids and terpenoids; ethyl acetate extract contains alkaloids, steroids and terpenoids; acetone extract contains saponins, steroids, terpenoids and tannins; 96% ethanol extract contains alkaloids, flavonoids, saponins, terpenoids, and tannins; and finally the chloroform extract of garlic skin contains alkaloids, steroids, terpenoids and tannins. So it can be concluded that the secondary metabolites in garlic peel extract contain alkaloids, flavonoids, saponins, steroids, terpenoids and tannins.the study, methods, results and conclusions, can describe qualitatiive and quantitative information.